Soil microbial biomass and community responses to long-term tillage and fertilizer regimes in corn under corn-winter wheat rotation - Gumisiriya, Costa; Kármen Juhász, Evelin; Kremper, Rita; Béni, Áron; Balla Kovács, Andrea (Acta Agraria Debreceniensis, 2026)
Agrotechnical interventions, namely, tillage and fertilization have a great influence on soil microbial activities and biomass, hence it is important to investigate their effect in long-term experiments. This study aimed at evaluating the impact of long-term tillage and NPK mineral fertilizer application on soil microbiological parameters in corn grown under corn-winter wheat rotation. The soil samples were collected in June of 2024 from the long-term experiment of the University of Debrecen at Látókép established in 1991. The treatments included control (no fertilizer), NPK fertilization (160 kg ha-1 N, 60 kg ha-1 P2O5, 90 kg ha-1 K2O) and tillages (Moldboard tillage-MT, Strip tillage-ST and Ripper tillage-RT). The soil microbial biomass and composition of its community (Actinomycetes, saprophytic fungi, Gram-positive bacteria, Arbuscular mycorrhizal fungi, Gram-negative bacteria) was measured by PLFA analysis of soil extract. Results indicate that NPK fertilization affected only the biomass of Arbuscular mycorrhizal fungi and Actinomycetes, whereas tillage greatly influenced the soil microbial biomass and community composition for all the microbial groups. Generally, the microbial biomass and community composition were highest under RT followed by ST and lowest under MT. In conclusion, conservation tillages are more favorable for soil microbial life than conventional tillage.